2009
DOI: 10.1074/jbc.m109.050419
|View full text |Cite
|
Sign up to set email alerts
|

The Smooth Muscle Cell-restricted KCNMB1 Ion Channel Subunit Is a Direct Transcriptional Target of Serum Response Factor and Myocardin

Abstract: Large conductance calcium-activated potassium (MaxiK) channels play a pivotal role in maintaining normal arterial tone by regulating the excitation-contraction coupling process. MaxiK channels comprise ␣ and ␤ subunits encoded by Kcnma and the cell-restricted Kcnmb genes, respectively. Although the functionality of MaxiK channel subunits has been well studied, the molecular regulation of their transcription and modulation in smooth muscle cells (SMCs) is incomplete. Using several model systems, we demonstrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 72 publications
2
49
0
Order By: Relevance
“…Each of these beta subunits plays a unique role in defining channel activation/deactivation rates and regulating Ca 2ϩ sensitivity (6), thereby defining the functional properties of BK Ca channels in a cell-specific manner (73). The activating beta 1 isoform, Kcnmb1, is restricted to smooth muscle, exhibits high Ca 2ϩ sensitivity and is slow to deactivate (26,44). We found that this isoform is significantly enriched in the DA compared with the AO.…”
Section: Discussionmentioning
confidence: 67%
“…Each of these beta subunits plays a unique role in defining channel activation/deactivation rates and regulating Ca 2ϩ sensitivity (6), thereby defining the functional properties of BK Ca channels in a cell-specific manner (73). The activating beta 1 isoform, Kcnmb1, is restricted to smooth muscle, exhibits high Ca 2ϩ sensitivity and is slow to deactivate (26,44). We found that this isoform is significantly enriched in the DA compared with the AO.…”
Section: Discussionmentioning
confidence: 67%
“…This gene, a potassium large conductance calcium-activated channel family member on chromosome 10q22.3, has been reported to be fundamental to the control of smooth muscle tone and neuronal excitability. [31][32][33] In our patient the RUNX1-KCNMA1 fusion, as confirmed by RT-PCR and Sanger sequencing, led to the disruption of the 'Runt homology domain' (RHD) of RUNX1 (Figure 4b). The break point in RUNX1 was detected in intron 3-4 (ENST00000300305), whereas in t(8;21) the genomic break point is located in intron 5, after the RHD domain.…”
Section: Targeted Next-generation Sequencing In Leukemia V Grossmann mentioning
confidence: 99%
“…Western Blotting-Cells were rinsed with phosphate-buffered saline (PBS) twice, and protein was extracted in cold lysis buffer containing 1% protease inhibitor mixture (Sigma) as described (43). Protein concentration was determined by a detergent-compatible protein assay (Bio-Rad).…”
Section: Methodsmentioning
confidence: 99%
“…Ϫ⌬⌬Ct method for normalization of raw data as described (43). The primers used for different target mRNA and miRs are listed in supplemental Table 1.…”
Section: Methodsmentioning
confidence: 99%